Análise dos modos de vibração e de frequências naturais de vigas em concreto armado através do método dos elementos finitos - Coelho, Eduardo Raique Soares (2025)
Dynamic analysis is crucial in structural projects in civil construction. In this sense, this work aimed to analyze, model, and simulate, in the Ansys® 2019 R3 software, the dynamic behavior of simply supported beams. Data from standards, such as NBR 6118:2014 and NBR 6118:2023, were used to define the mechanical characteristics of the model. The first stage involved the modal and parametric analysis of three reinforced concrete beams (isotropic elastic) simply supported with one support of the first kind and another of the second kind, determining the vibration modes and their respective natural frequencies. It was concluded that the modal analysis performed in Ansys for beams presented modal frequencies with values close to the parametric analysis performed through computer programming in Python. In the second stage, the results of the modal analysis of the three simply supported reinforced concrete beams were compared with Table 23.1 of the NBR 6118:2023 standard. The results were satisfactory for all vibration modes and their respective natural frequencies, thus indicating compliance with the parameters of the Standard table for the first, second and third vibration modes of the three beams. If some of these natural frequencies were not in accordance with the Standard parameters, the solutions found would be to increase the cross section, reinforce with polymer composites and apply metal structures together with reinforced concrete. All numerical analyses were performed with a 1 cm mesh study. Validation of the analysis by Ansys® 2019 R3 paves the way for applications in more complex structures. This analysis is crucial for structures under dynamic loads, preventing resonance. Computational tools and non-destructive testing are essential for rehabilitation decisions. The results obtained are valuable and satisfactory, providing a significant level of confidence in the studies performed.